The Influence of Brand Ambassadors on Brand Image and Purchase Decisions for Nike Shoes in Mataram City - Junarta, Harbyanto; Sulaeman, Sulaeman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study intends to determine the impact of the brand minister on brand image and the choice to purchase Nike brand shoes in the city of Mataram. This kind of exploration includes cooperative examination because this research means to determine the impact or relationship between two or more factors. The factors in this research are brand minister, brand image, and purchasing choices. The information sorting technique used is a review test strategy. The population in this exploration is Mataram city residents aged > 18 years who have purchased Nike brand sports shoes as before, and chose to buy their own Nike shoes. Get the purposive testing test method, with complete examples of 100. The right poll goes directly to where the exploration is carried out. The information checking tool used is Multivariate. Relapse Investigation uses the Incomplete Least Square (PLS) strategy and is assisted by the smartPLS 3.0 information handling instrument.The research results show that (1) brand ambassadors have a significant influence on brand image. (2) Brand ambassadors have a significant influence on purchasing decisions. (3) brand image has a significant effect on purchasing decisions